Penerapan Teori Situasi Didaktis untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Kelas V Sekolah Dasar - Simanjuntak, Millenia; Putra, Zetra Hainul; Antosa, Zariul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This study aims to determine the effect of the application of didactic situation theory in improving the mathematical problem-solving ability of fifth grade elementary school students on the subject of comparing distance, time and speed. This study uses a quasi-experimental method with pretest and posttest which are forms of formative evaluation used to determine the progress or development of student learning. The study was conducted at SDN 136 Pekanbaru in the odd semester of the 2023/2024 school year. The results of this study indicate that there is a significant effect on students' mathematical problem-solving ability with the application of didactic situation theory in fifth grade elementary school.